Effect of Mild Treatments on Some Physicochemical and Pasting Characteristics of Flour from Two Cocoyam Cultivars: Treatment Effects on Cocoyam Flour (Biological Sciences - PJSIR, 2011)
Effect of mild treatments namely; one-step annealing (AN), partial-nixtamalization (NIX) and phenolic-admixture (VAN) on some physicochemical and pasting characteristics of flour prepared using two cocoyam cultivars was studied. Both annealing treatment and phenolic admixture resulted in high peak viscosities (PVANwhite = 322.50 RVU; PVVAN             = 306.67 RVU) of samples comparative to low peak viscosity white = 227.25 RVU) of the control for white cultivar. Similarly, the peak viscosities (PV red =   310.70; PVVANred  = 296.45) of samples were higher than the peak viscosity (PVred         = 225.42 RVU) of the control for red cultivar. Assessment revealed positive set back viscosities (SBVAN = + 9.30 RVU; SBVAN                = + 21.33 RVU) for both the varieties after annealing treatment. Partial- NIX treatment showed molecular depolymerization. Interaction of treatments at levels employed in this study showed no synergistic effect. The pH of treated and control samples were within low acid range for foods. Mild treatment could be useful for tempering cocoyam flour for preparation of bakery and similar pasta products.